Interventions to address health outcomes among autistic adults: A systematic review. (August 2020) - Benevides, Teal W; Shore, Stephen M; Andresen, May-Lynn; Caplan, Reid; Cook, Barb; Gassner, Dena L; Erves, Jasmine M; Hazlewood, Taylor M; King, M Caroline; Morgan, Lisa; Murphy, Lauren E; Purkis, Yenn; et al.
Research has shown that autistic adults have poor health outcomes. We conducted a systematic review to identify existing interventions to address health outcomes for autistic adults and to determine whether these interventions address the priorities of the autistic community. We searched PubMed for articles that included an intervention, a primary health outcome measured at the individual (not system) level, and a sample population of at least 50% autistic adults. Studies were excluded if they were not peer-reviewed, had a focus on caregivers, were expert opinions on specific interventions, untested protocols, or interventions without a primary health outcome. Out of the 778 articles reviewed, 19 were found to meet the stated criteria. Based on the evidence gathered, two were considered emerging evidence-based approaches: cognitive behavioral approaches and mindfulness. The remaining interventions included in the review did not have sufficient evidence to support current use with this population. The majority of the studies included samples of young autistic adults, primarily male, without an intellectual disability. Anxiety, quality of life, depression, and behavioral issues were among the health outcomes measured in the final included articles. More research on preferred interventions with prioritized health outcomes of the autistic adult population is needed. Lay abstract: Autistic adults have more health problems then their same-aged peers. Yet little research has been conducted that focuses on addressing these health problems. In order to guide future research, it is important to know what intervention studies have been done to improve health outcomes among autistic adults. The project team and student assistants read studies that were published between 2007 and 2018 in the online research database, PubMed. We looked for studies published in English, which were peer-reviewed and included (1) an intervention, (2) an outcome that was related to health, and (3) a study group that included autistic adults. We did not include studies that had outcomes about employment (unless there was a health outcome), studies about caregivers or caregiving, or expert opinions about interventions. Of 778 reviewed articles, 19 studies met all of the criteria above. Within these studies, two approaches were found to have emerging evidence for their use in autistic adults: cognitive behavioral interventions and mindfulness-based approaches for improved mental health outcomes. The remaining intervention approaches did not have enough articles to support their use. Many of the outcomes were about reduced symptoms of co-occurring mental health diagnoses (e.g. reduced anxiety, depression). Most of the participants in these studies were male and did not have intellectual disability. Most study participants were adults younger than 40. There are not many intervention studies that address health outcomes among autistic adults. More research is needed on interventions which are desired by the adult autism community and address preferred health outcomes such as increased quality of life or well-being.